Long-term behavior of GFRP pipes: Optimizing the distribution of failure points during testing. (December 2015) - Na, Liang; Sirong, Zhu; Jianzhong, Chen; Xi, Fang
Abstract: The certification of glass-fiber reinforced plastic (GFRP) piping systems is regulated by normative standards in which test series of 10, 000 h are needed to predict the residual property of the expected life (normally, 50 years). In this paper, optimization of statistical distribution of the test is proposed. This system involves using orthogonal design and test schemes lasting under 10, 000 h. Experimental results for long-term ring-bending strain (S b ) of GFRP pipes from the standard test procedure indicated that this system is practical and effective. The estimation error when using the proposed method was consistently less than 8% if compared to the standard method.